Bank strategy in consumer credit market and mechanism on its implementation - Jiang Hai (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The Object of Research: Corporate credit business in commercial banks, focusing on SP Bank Z Branch. The Subject of Research: Development strategy of the corporate credit business at SP Bank Z Branch, analysing its challenges, environment, and optimization methods. The Purpose of Qualification Master's Work: To identify key problems and challenges in SP Bank Z Branch’s corporate credit business, explore their causes, and propose strategies to improve the quality, efficiency, and sustainability of its credit operations. Based on the results of the research: The research identified key challenges in SP Bank Z Branch's corporate credit business, such as complex processes, insufficient innovation, and fierce industry competition. Based on the findings, strategies have been proposed to optimize customer structures, strengthen risk management, and enhance service systems, ensuring sustainable growth and competitiveness.
Стратегія банку на ринку споживчого кредитування та механізм її реалізації
Scientific adviser: Samorodov Borys, doctors of economics, professor,
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; corporate credit; commercial banks; SP bank Z branch; credit; risk management; strategic development; banking industry competition; customer structure optimization; macro-environmental analysis